If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -12 = 5x + -10 Reorder the terms: -12 + 3x = 5x + -10 Reorder the terms: -12 + 3x = -10 + 5x Solving -12 + 3x = -10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -12 + 3x + -5x = -10 + 5x + -5x Combine like terms: 3x + -5x = -2x -12 + -2x = -10 + 5x + -5x Combine like terms: 5x + -5x = 0 -12 + -2x = -10 + 0 -12 + -2x = -10 Add '12' to each side of the equation. -12 + 12 + -2x = -10 + 12 Combine like terms: -12 + 12 = 0 0 + -2x = -10 + 12 -2x = -10 + 12 Combine like terms: -10 + 12 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| 2x^2+3=6x-1 | | 3x/4=27 | | x+(x*0,2)=100 | | 64-3x=6x+21 | | 8q-9/3=46 | | 4x^2-152x+704=0 | | 2y^2-8y=-5 | | (18x+13)-(15x-12)=x+9 | | 3(k-2)=k+2 | | 5x+6=-120-2x | | 3/4y=2/3y+5 | | 35y^4+20y^2-5y^5= | | 5(x-3)=3(x+7)-x | | x/8=(x/5)+(1/8) | | (16+x)2=27 | | 13x^2+5-[5(x^2-6)+6]=0 | | 4X+X/4=34 | | -x^2(-x^2)(-x^2)= | | 4i(2-5i)= | | 4a^7/a^3 | | 12+2y=2+5y | | 5y^2-21y-54=0 | | -24x^13/6x^4 | | 4/7+9/28 | | (-3u^(5/3))(-5u^(-2/3)) | | (-3u^5/3)(-5u^-2/3) | | X+5/2-8=2x-7/3 | | 2y^2=4+y^2 | | 4x/x-6x=1 | | x^2-9x=x-20 | | 5-8=157-36x | | X^2-5x=120 |